Development of a Mobile Device Optimized Cross Platform‐Compatible Oral Pathology and Radiology Spaced Repetition System for Dental Education. Issue 4 (1st April 2015) - Al‐Rawi, Wisam; Easterling, Lauren; Edwards, Paul C.
Abstract : Combining active recall testing with spaced repetition increases memory retention. The aim of this study was to evaluate and compare students' perception and utilization of an electronic spaced repetition oral pathology‐radiology system in dental hygiene education and predoctoral dental education. The study employed an open‐source suite of applications to create electronic "flashcards" that can be individually adjusted for frequency of repetition, depending on a user's assessment of difficulty. Accessible across multiple platforms (iOS, Android, Linux, OSX, Windows) as well as via any web‐based browser, this framework was used to develop an oral radiology‐oral pathology database of case‐based questions. This system was introduced in two courses: sophomore oral pathology for dental students and sophomore radiology for dental hygiene students. Students were provided free software and/or mobile tablet devices as well as a database of 300 electronic question cards. Study participants were surveyed on frequency and extent of use. Perception‐based surveys were used to evaluate their attitudes towards this technology. Of the eligible students, 12 of 22 (54.5%) dental hygiene and 49 of 107 (45.8%) dental students responded to the surveys. Adoption rates and student feedback were compared between the two groups. Among the respondents, acceptance of this technology with respect to educational usefulness was similar for the dental and dental hygiene students (median=5 on a five‐point scale; dental hygiene interquartile range (IQR)=0; dental IQR=1). Only a minority of the survey respondents (25% dental, 33% dental hygiene) took advantage of one of the main benefits of this technology: automated spaced repetition.